BIMBINGAN KELOMPOK MELALUI TEKNIK ROLE PLAYING TERHADAP PERILAKU BULLYING SISWA SMA - Irma Wulandari; Rima Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2019)
The purpose of this research  was to determine the use of group guidance services with role playing techniques to overcome the bullying behavior of high school students.  Bullying behavior is a problem that is often faced by adolescent peer refusal to lead to the emergence of bullying behavior in students.  Increased cognitive abilities and awareness of adolescents can prepare teens to deal with stress and emotional fluctuations effectively, many adolescents cannot manage their emotions effectively.  As a result, adolescents are prone to anger, less able to control emotions, which can then lead to the emergence of various problems with negative emotions, one of which is bullying.  The method used in this research is a literature review that refers to previous studies and based on data from related sources.  Based on the results of several previous studies indicate that the implementation of group guidance with effective role playing techniques and helps in overcoming the bullying behavior of high school students.Keywords:    Bullying, Group Guidance, Role Playing